Pharmacokinetics of concomitant cisplatin and paclitaxel administered by hyperthermic intraperitoneal chemotherapy to patients with peritoneal carcinomatosis from epithelial ovarian cancer - Ansaloni, L (Br J Cancer, 2015)
BACKGROUND: Hyperthermic intraperitoneal chemotherapy (HIPEC) is advised as a treatment option for epithelial ovarian cancer (EOC) with peritoneal carcinomatosis. This study was designed to define the pharmacokinetics of cisplatin (CDDP) and paclitaxel (PTX) administered together during HIPEC. METHODS: Thirteen women with EOC underwent cytoreductive surgery (CRS) and HIPEC, with CDDP and PTX. Blood, peritoneal perfusate and tissue samples were harvested to determine drug exposure by high-performance liquid chromatography and matrix-assisted laser desorption ionization imaging mass spectrometry (IMS). RESULTS: The mean maximum concentrations of CDDP and PTX in perfusate were, respectively, 24.8±10.4 μg ml(−1) and 69.8±14.3 μg ml(−1); in plasma were 1.87±0.4 μg ml(−1) and 0.055±0.009 μg ml(−1). The mean concentrations of CDDP and PTX in peritoneum at the end of HIPEC were 23.3±8.0 μg g(−1) and 30.1±18.3 μg(−1)g(−1), respectively. The penetration of PTX into the peritoneal wall, determined by IMS, was about 0.5 mm. Grade 3–4 surgical complications were recorded in four patients, five patients presented grade 3 and two patients presented grade 4 hematological complications. CONCLUSIONS: HIPEC with CDDP and PTX after CRS is feasible with acceptable morbidity and has a favorable pharmacokinetic profile: high drug concentrations are achieved in peritoneal tissue with low systemic exposure. Larger studies are needed to demonstrate its efficacy in patients with microscopic postsurgical residual tumours in the peritoneal cavity.